A COMPARATIVE ANALYSIS OF PRACTICAL CLASSES IN CELLULAR BIOLOGY FOR UNDERGRADUATE BIOLOGICAL SCIENCES STUDENTS - Rocha, Thiago Lopes; de Oliveira, Mayara Lustosa; Seraphin, José Carlos; Sabóia-Morais, Simone Maria Teixeira (Investigações em Ensino de Ciências, 2016)
The purpose of this study is to perform a comparative analysis of the views of first year undergraduate students in Biological Sciences concerning practical classes in cellular biology. The results indicate that the subject is fundamental in the training of future biologists. Practical classes are the means to apply theory taught previously and may lead to alterations in views on relevant topics. Static viewing as well as equality noting between cell types are examples of conceptions modified due to the application of distinct methodological practices. The application of a questionnaire showed that views differed in bachelor of science (BS) Teacher Certification (TC) classes. The BS students preferred practical classes using the light microscope, while TC students preferred classes where visual devices such as movies and /or animation were used. We suggest that practical classes in cellular biology be prepared differently, according to each type of biology course.